2023
DOI: 10.1186/s40001-023-01208-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of a selective urate reabsorption inhibitor dotinurad in patients with hyperuricemia and treated hypertension: a multicenter, prospective, exploratory study (DIANA)

Abstract: Introduction Dotinurad is a newer urate-lowering agent that selectively inhibits urate transporter 1 in the renal proximal tubule and increases urinary urate excretion. Currently, little is known about the clinical efficacies of dotinurad in patients with hyperuricemia and hypertension. The aim of this study was to assess the clinical effects of a selective urate reabsorption inhibitor dotinurad on serum uric acid (SUA) levels and relevant vascular markers in patients with hyperuricemia and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…However, a sub-analysis of the above study found that topiroxostat reduced CAVI in a sub-population with liver dysfunction [26]. On the other hand, dotinurad, a urate reabsorption inhibitor, also reduced CAVI despite not inhibiting xanthine oxidase [27]. Considering these previous reports indicating that the inhibition of xanthine oxidase is not necessarily required to improve CAVI, it seems less relevant to consider SUA as just an atherogenic marker.…”
Section: Discussionmentioning
confidence: 79%
“…However, a sub-analysis of the above study found that topiroxostat reduced CAVI in a sub-population with liver dysfunction [26]. On the other hand, dotinurad, a urate reabsorption inhibitor, also reduced CAVI despite not inhibiting xanthine oxidase [27]. Considering these previous reports indicating that the inhibition of xanthine oxidase is not necessarily required to improve CAVI, it seems less relevant to consider SUA as just an atherogenic marker.…”
Section: Discussionmentioning
confidence: 79%
“…When the CAVI was incorporated into a model with known CVD risks for predicting CV events, the global χ2 value increased, suggesting that the CAVI predicted CV events. The 24-week treatment with dotinurad significantly reduced the CAVI from 9.29 to 8.92 ( p = 0.044), suggesting that dotinurad may favorably affect arterial stiffness [ 15 ]. The derivatives of the reactive oxygen metabolite concentration at week 24 were significantly lower than those at the baseline [ 15 ].…”
Section: The Association Of Urat1 and Other Ua Transporters With The ...mentioning
confidence: 99%
“…The 24-week treatment with dotinurad significantly reduced the CAVI from 9.29 to 8.92 ( p = 0.044), suggesting that dotinurad may favorably affect arterial stiffness [ 15 ]. The derivatives of the reactive oxygen metabolite concentration at week 24 were significantly lower than those at the baseline [ 15 ]. URAT1 inhibition by dotinurad at the urate entry site on the vascular walls and the resultant attenuation of ROS production might have caused such beneficial vascular effects [ 103 , 104 ].…”
Section: The Association Of Urat1 and Other Ua Transporters With The ...mentioning
confidence: 99%
See 1 more Smart Citation